COMPARISON OF FLOW PATTERNS IN THE RADIOCEPHALIC ARTERIOVENOUS FISTULA THROUG IN VITRO AND IN SILICO STUDY - Oliveira, F. C. M.; Bessa, K. L.; Moreira, R. W. C. (Revista de Engenharia Térmica, 2015)
The vascular accesses to hemodialysis patients usually are through arteriovenous fistula (AVF) or synthetic grafts. The analyses of recirculation zones, stagnation points, secondary flow and low and high shear stress are very important points to study for understand the hemodynamic local in arteriovenous fistula. In this work, it was analyzed through computational fluid dynamics the streamlines in AVF and it was compared with the literature results. The flow patterns were visualized under steady and unsteady condition with Reynolds number ranging from 100 up 600. The results obtained from CFD were very similar with the literature results. The flow becomes more chaotic when the Reynolds number increases. Vortex can be seen in anastomosis region, occupying all transversal section of the artery. Thus, the results obtained using CFD look like the results obtained experimentally.